2017
DOI: 10.21315/mjms2017.24.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Cell Morphology in Keratoconus: A Confocal Microscopic Observation

Abstract: Purpose: To evaluate corneal cell morphology in patients with keratoconus using an in vivo slit scanning confocal microscope.Methods: A cross-sectional study was conducted to evaluate the corneal cell morphology of 47 keratoconus patients and 32 healthy eyes without any ocular disease. New keratoconus patients with different disease severities and without any other ocular co-morbidity were recruited from the ophthalmology department of a public hospital in Malaysia from June 2013 to May 2014. Corneal cell morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…It is very difficult to found any abnormal of cornea by slit lamp in the stage of preclinical stage of keratoconus. Some research mentioned the fold near Descement membrane [16][17][18]. In our study we found black fold near Descement membrane in almost all eyes, especially in patients with keratoconus.…”
Section: Discussionsupporting
confidence: 57%
“…It is very difficult to found any abnormal of cornea by slit lamp in the stage of preclinical stage of keratoconus. Some research mentioned the fold near Descement membrane [16][17][18]. In our study we found black fold near Descement membrane in almost all eyes, especially in patients with keratoconus.…”
Section: Discussionsupporting
confidence: 57%
“…All corneal layers show histopathological structural changes in KC (Khaled et al 2017). Studies have shown that basal epithelial cells in KC patients displayed enlargement, irregular arrangement, and a significant reduction in cell density when compared to healthy individuals (Ghosh et al 2017). Other studies demonstrated either no significant change of corneal epithelium (Erie et al 2002) or thickened corneal epithelium in KC patients (Hollingsworth et al 2005;Weed et al 2007;Bitirgen et al 2015).…”
Section: Clinical Aspects Of Injury and Diseasementioning
confidence: 98%
“…On the other hand, Ghosh and his colleagues demonstrated that, the corneal cell morphology of cases with KC varied significantly from the healthy ones except in ECD (P=0.072) (17) .…”
Section: Discussionmentioning
confidence: 95%